Analysis of the Effectiveness of Virtual Reality as an Innovative Media in Learning Islamic History in Higher Education: A Literature Review - Islam, Firaunal; Tuzzahrah, Fatimah; Tahir, Fitrah Pratiwi; Hastuty, Ade (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to assess the effectiveness of Virtual Reality (VR) as an innovative learning medium in Islamic History courses at universities. The main issue raised is the low level of student interest and understanding due to conventional teaching methods that tend to be abstract. This study uses a qualitative research method with a literature study approach, examining reputable journals and academic books published between 2020 and 2025 that are relevant to the use of VR in education. The results show that VR can improve understanding of historical concepts, motivate students, and encourage active engagement through immersive learning experiences. Previous studies also confirm that VR helps students understand historical contexts more realistically, strengthens historical thinking skills, and improves information retention. Additionally, this technology supports andragogical learning and student-centered approaches. This study demonstrates that VR has great potential as a strategic medium for deepening the learning of Islamic History.